Assessment of Storm Water Quality in Grass Swale by Using Sand Filter Media: a Case Study at UTHM Campus - Yusoff, Mohd. Azlan B. Mohd; Gheethi, Adel Al-; Dzain, Daniel Aizat B. (International Journal of Engineering and Technology, 2018)
Urbanization in Malaysia has contributed to the increased of volume runoff to the drainage system. SUDS (Sustainable Urban Drainage System) / MSMA (Manual Saliran Mesra Alam) has been implement in Malaysia within several of components. Hence, swale is one of the designed and suggested by SUDS or MSMA in order to control the quantity and quality storm water runoff. The present study aimed to determine the quality of storm water runoff in swale and to analyse storm water runoff treatment using sand column as a part of filtration process.Â Water quality parameters tested included COD, BOD5, DO and TSS. The samples was test with sand column on D30, D60, D90 and DMIX. The results revealed that sand column improved the water quality by 4% to 80%. In conclusion, the sand column can be used to improve the storm water quality and can enhance the natural habitat.